Inovasi Pengolahan Limbah Baglog Jamur Tiram Menjadi Kompos Dengan Mol Nasi Basi Sebagai Bioaktivator - Febrianti, Nia; Basransyah; Safitri, Nuri Dwi (LPPM ITK, 2025)
Oyster Mushroom Cultivation at KM 15, Balikpapan City produces up to 4,000 kg of baglog waste within a 3-month period. The baglog waste, which serves as the growing medium for oyster mushrooms, is merely stacked and discarded into the surrounding forest without proper treatment. Accumulation of baglog waste can cause environmental pollution as it becomes a breeding ground for wild fungi. Composting offers a potential solution for managing baglog waste. The composting process requires the addition of an activator to accelerate decomposition, such as fermented rice-based Local Microorganisms (MOL), which contain Lactobacillus sp. and Saccharomyces sp. Rice-based MOL is rich in carbohydrates, which serve as nutrients for microorganisms. This study aims to analyze the quality of compost produced from oyster mushroom baglog waste using rice-based MOL as a bioactivator, as well as to determine the effect and optimal volume of MOL on compost quality. The composting process was carried out using the aerobic Takakura method at a laboratory scale over a 30-day period. The variations of rice-based MOL used were 0 mL, 100 mL, and 250 mL. The quality of the resulting compost was compared against the Indonesian National Standard (SNI) 19-7030-2004. The results of the study showed that the control treatment, as well as the addition of 100 mL and 250 mL of MOL, met the compost quality standards for temperature, pH, odor, color, texture, moisture content, nitrogen, phosphorus, organic carbon, and C/N ratio. However, the potassium parameter did not meet the standard. Based on the graph, the addition of rice-based MOL indicates a positive effect on compost quality improvement. The optimum MOL volume for all parameters was 250 mL, although the potassium parameter still did not meet the SNI 19-7030-2004.